Textbook Evaluation Of English For Education In ESP: Smart Grammar and Vocabulary - Abdul Syahid; Ayu Putriana Lestari; Nazwa Maulani Dewi; Siti Nurrahmah; Yulis Setiawati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study aims to evaluate the effectiveness of English textbooks for special purposes, particularly in the context of learning English for education. The content analysis method was used to evaluate the textbook with a focus on its purpose, content, methodology, and practical aspects. The results of the analysis showed strengths in purpose, approach, design and organization, as well as language aspects such as vocabulary and grammar. However, there were weaknesses in content coverage and integration of important components such as grammar and pronunciation. The implication is that this study emphasizes the importance of textbook evaluation to ensure the quality and effectiveness of learning, by adapting the materials to learners' needs and integrating methodologies that are in line with the latest educational developments.